Spatial and temporal variation in the migration of Ruddy-headed Goose in southern South America using satellite tagging - Pedrana, Julieta (2020)
Ruddy-headed Goose Chloephaga rubidiceps is the smallest of the five South American sheldgeese and has two separate populations: one sedentary, which resides in the Malvinas/Falkland Islands and one migratory that overwinters mainly in the Pampas region, Argentina and breeds in Southern Patagonia. The Ruddy-headed Goose’s continental population has decreased considerably, and recent estimates indicated that the population size is less than 800 individuals. In Argentina and Chile, this population is categorised as endangered. Understanding migration across vast landscapes is essential for the identification of factors affecting the survival of this endangered population and for the application of effective conservation measures. We aim to provide the first documentation of the complete migration cycle of Ruddy-headed Goose, and to analyse their annual migration in detail, including identification of stop-over, breeding and wintering sites, and to compare migration timing during spring and autumn migration. Adults were captured in the southern Pampas and equipped with solar satellite transmitters in 2015 and 2016. We analysed the influence of season (spring vs autumn migration) on the number and duration of stop-overs, distance travelled and overall migration speed using Generalized Linear Mixed Models. Our results showed that tracked geese used the eastern Patagonian route to reach their breeding grounds and take the same route after breeding. Spring migration was significantly faster than autumn migration, at least based on the number of days spent in their stop-overs. Stop-overs were closer to the final destination, either during spring and autumn migrations, though some of them were not used during subsequent migrations. Our migration cartography for Ruddy-headed Geese, together with the timing and location data, should be used to improve conservation efforts directed at this species and might contribute to the modification of the current status of ‘Least Concern’ under the IUCN criteria.